Nonsingular Terminal Sliding Mode Control-based Prescribed Performance Guidance Law with Impact Angle Constraints - Ming, Chao; Wang, Xiaoming (International journal of control, automation, and systems, 2022)
Conventional guidance law designs can only guarantee steady-state performance. However, transient performance is also the key performance index in practical guidance applications. In this paper, a novel terminal guidance law is presented for missile intercepting maneuvering target with impact angle constraints, which can strictly guarantee the prescribed steady-state and transient performances of interception. By utilizing the prescribed performance control technique, the prescribed performance tracking control problem is transformed into an equivalent unconstrained form such that the tracking error can be limit to the prescribed performance bound. Then, on the basis of transferred the tracking error, a novel nonsingular terminal sliding mode control-based guidance law is proposed with impact angle constraint, and the extended state observer is incorporated to online estimate the external disturbances and unknown target maneuver. The closed-loop system stability and the convergence characteristic are rigorously proved. Finally, extensive contrast simulations are conducted to demonstrate the efficiency and superiority of the proposed guidance law for different engagement scenarios.